The Theological Implication of Oceanography Concept in the Qur'an - Ahmad Husnul Hakim; Amiril Ahmad (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2023)
The integration of science and the Qur’an, known as scientific exegesis (tafsīr ‘ilmī), has emerged as a crucial interpretative model in response to the division between secular and religious knowledge. This study delves into Qur’anic verses related to oceanography, exploring their theological significance and uncovering numerous benefits of the oceans, including their roles as sources of life, climate regulators, livelihood providers, and transportation channels. Additionally, it identifies a remarkable 38 verses discussing oceanography, with 18 of them emphasizing key theological messages such as the exclusive divinity of God, His role as the Creator and Controller of all, the submission of nature to Him, the vastness of His knowledge, and His undeniable greatness. Ultimately, the Qur’anic concept of oceanography reaffirms the existence of God as the Creator and emphasizes humanity’s responsibility as His creatures and servants, tasked with worshiping and glorifying Him. This fusion of science and the Qur’an offers valuable alternative interpretations that can enhance human understanding.